The Conceptions of Divine Revelation: A Comparative Study of the Views of Ibn Sina and Mulla Sadra - HosseiniEskandian, Abdullah; Setiyani, Wiwik; Muktafi, Muktafi; Kholid, Abd; Babaei, Ali (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
The issue of revelation is one of the most important issues in the divine religions. In Islam the issue revelation is of central importance, as the revealed word of God, the Qur’ān, is in itself a miracle in its inimitability, a unique masterpiece of the divine message that cannot be replicated. Revelation is understood as communication from the unseen world above, whereby God issues His divine commands to humankind. The eminent Muslim philosophers Ibn Sina and Mulla Sadra discussed the concept of revelation in their works. Ibn Sina considered revelation as a specific sensory effect on the prophet’s consciousness, whereby the Angel of Revelation cast the divine words into the prophet’s heart. Mulla Sadra also considered revelation as a type of unseen form of communication, whereby the divine commands are shared with humankind. This article attempts to study the nature of revelation, the levels of revelation, and the manner of revelation from the point of view of Ibn Sina and Mulla Sadra through a descriptive-analytical method. Ibn Sina and Mulla Sadra, despite their differences in conceptualizing and explaining the process of revelation, agreed that the revealed message is from God directly, without the independent agency of the Angel of Revelation and the prophets, who only carry and receive the divine message, yet cannot alter it.